(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
In this comprehensive article, the author delves into the realm of syntactic stylistic devices, elucidating their significance in language and communication. The article meticulously dissects various devices such as parallelism, chiasmus, anaphora, ellipsis, asyndeton, and more, highlighting their unique contributions to literary expression. Each device is illustrated with vivid examples from renowned speeches, literature, and iconic texts, demonstrating their impact on rhythm, emphasis, and emotional resonance. Furthermore, the author goes beyond the commonly known devices, shedding light on nuanced elements like inversion, polysyndeton, zeugma, parenthesis, hypotaxis, parataxis, and syllepsis. Through these additional explanations, the article offers a comprehensive understanding of how writers and orators employ syntactic devices to create depth, evoke emotions, and engage readers or listeners.